2019
DOI: 10.5395/rde.2019.44.e18
|View full text |Cite
|
Sign up to set email alerts
|

A micro-computed tomographic study of remaining filling materials of two bioceramic sealers and epoxy resin sealer after retreatment

Abstract: Objective This study evaluated the presence of residual root canal filling material after retreatment using micro-computed tomography (micro-CT). Materials and Methods Extracted human teeth (single- and double-rooted, n = 21/each; C-shaped, n = 15) were prepared with ProFile and randomly assigned to three subgroups for obturation with gutta-percha and three different sealers (EndoSeal MTA, EndoSequence BC sealer, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 35 publications
(44 reference statements)
2
40
0
Order By: Relevance
“…These studies [11,28,30] attribute this difference to the fact that EndoSequence BC has the potential to penetrate dentinal tubules, leave intratubular tags, and adhere to canal walls [9,27,[31][32][33][34]. Studies comparable to those mentioned in the previous sentences [9,11,27,28,[30][31][32][33][34] have found the opposite [35,36]. The removability of AH Plus and GP after cold lateral obturation was between 89% and 99% in some studies [20][21][22], while Ma et al reported a 96% removal of GP and iRoot SP sealer [19]; the iRoot SP sealer is identical to EndoSequence BC sealer [10].…”
Section: Discussionmentioning
confidence: 92%
“…These studies [11,28,30] attribute this difference to the fact that EndoSequence BC has the potential to penetrate dentinal tubules, leave intratubular tags, and adhere to canal walls [9,27,[31][32][33][34]. Studies comparable to those mentioned in the previous sentences [9,11,27,28,[30][31][32][33][34] have found the opposite [35,36]. The removability of AH Plus and GP after cold lateral obturation was between 89% and 99% in some studies [20][21][22], while Ma et al reported a 96% removal of GP and iRoot SP sealer [19]; the iRoot SP sealer is identical to EndoSequence BC sealer [10].…”
Section: Discussionmentioning
confidence: 92%
“…Many studies have been proposed the use of micro-CT for the evaluation of endodontic materials [ 1 3 4 12 20 21 22 ]. Micro-CT allows a nondestructive, quantitative and qualitative high-resolution imaging-based assessment [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Micro-computed tomography (micro-CT) is a 3-dimensional (3D) nondestructive and reproducible tool that is highly accurate for the evaluation of root canal filling quality and the presence of voids [ 3 9 10 11 ]. Many studies have focused on evaluating the material/dentin using 3D information using micro-CT, but have presented significant variation in the reported voxel sizes used for scanning [ 3 5 12 13 14 ].…”
Section: Introductionmentioning
confidence: 99%